17. EFFECT OF BILE ACID AND PANCREATIC JUICE IN REFLUX ESOPHAGITIS AFTER TOTAL GASTRECTOMY IN RAT MODEL. (24th September 2022) - Hashimoto, Naoki
Abstract: Esophagitis after total gastrectomy has been associated with the reflux of duodenal content into the esophagus. This study is to determine which fraction of the duodenum content reflux, pancreatic juice or bile acids contributes to the development of reflux esophagitis. 8 week Wistar Rats were used. 1. Reflux of Pancreatic juice and Bile(TG):End-to-end esophago-duodenostomy with total gastrectomy (n = 8) 2. Reflux of Pancreatic Juice (TG + P):End-to-end esophago-duodenostomy with total gastrectomy. Then, a bypass operation of the upper bile duct was made 25 cm below the esophagoduodenostomy anastomosis. Choledocho-jejunostomy was performed. (n = 6) 3. Reflux of Bile (TG + B) (n = 4):Roux-en-Y esophagojejunostomy with total gastrectomy. The bile duct was then divided and reimplanted into the proximal portion of the Roux limb, preceding the esophagojejunostomy to produce biliary reflux. Three weeks after, all rats were euthanized and the esophagus was evaluated histologically. 1. Macroscopy: In TG rats, the esophageal wall was thickened and covered with whitish nodular patches. The gross appearance of the esophagus from TG + P and TG + B group showed only scattered erosions. The ulcer score in TG + P and TG + B were significantly lowered compared to TG. 2. Microscopy: TG group developed large and long longitudinal ulcers. The inflammatory cell infiltration scores and hyperplasia scores were significantly decreased in the TG + B and TG + P group compared to TG group. The reflux of pancreatic juice alone and bile acid alone are not significant development of reflux esophagitis. Reflux of combined of bile acid and pancreatic juice to esophagus caused sever reflux esophagitis.